Surga Dan Neraka dalam Interpretasi Ibn ‘Arabi - jatim mistar (STIU Al-Mujtama Pamekasan, 2020)
The nature of heaven and hell basically still has several interpretations. Therefore the author will review thoroughly about the verses of heaven and hell, namely the tala'ah of the verses of heaven and hell from the perspective of Ibn 'Arabi> focused on Ibn' Arabi's interpretation of QS al-Ra'd verse 35 and al-A ' la> verses 12-13 about the meaning of heaven and hell with library research, as for the method of analyzing data researchers using descriptive analytical. The purpose of this study is to find out Ibn‘Arabi's interpretation of the meaning of heaven and hell. As a result of this research, Ibn ‘Arabi> said, heaven is a home of pleasure that is all eternal in it. Heaven is filled with food, drinks, weddings, clothes, fragrances, melodious singing and beaming faces with scenes filled with angels and surrounded by the shade of trees and clear flowing rivers. Whereas Hell according to Ibn ‘Arabi> is a place where in it is still accompanied by the love of Allah SWT. Like the pleasure or happiness that is likened to a person who dreams in his sleep, only his sleep does not change the place where he is, that is, remain in hell. Keywords: Heaven, Hell, Interpretation, Ibn Arabi